A case study investigating creative teaching strategies inspired by Waldorf education at a public high school in the Western Cape - Hofmeyr, Elizabeth Lona (Stellenbosch : Stellenbosch University, 2020)
Thesis (MA(VA))--Stellenbosch University, 2020.